Researching Emotion in Courts and the Judiciary : A Tale of Two Projects - Roach Anleu, Sharyn; Bergman Blix, Stina ; 0000-0003-3522-4963; Mack, Kathy (Emotion Review, 2015)
The dominant image of judicial authority is emotional detachment; however, judicial work involves emotion. This presents a challenge for researchers to investigate emotions where they are disavowed. Two projects, one in Australia and another in Sweden, use multiple sociological research methods to study judicial experience, expression, and management of emotion. In both projects, observational research examines judicial officers' display of emotion in court, while interviews investigate judicial emotional experiences. Surveys in Australia identify emotions judicial officers generally find important in their work; in Sweden, shadowing allows researchers to investigate individual judicial emotion experiences and expression. Evaluating the different methods used demonstrates the limitations and effectiveness of particular research designs, the value of multiple methods and the challenges for researching emotion.
AuthorCount:3; 2017-11-13T21:27:07.074+01:00
Keywords: courts; emotions; multiple methods; the judiciary; Psychology; Psykologi; Sociology; Sociologi; courts, emotions, multiple methods, the judiciary